2005
DOI: 10.1007/11573548_81
|View full text |Cite
|
Sign up to set email alerts
|

An Emotion Model of 3D Virtual Characters in Intelligent Virtual Environment

Abstract: Abstract. Human emotion is related to stimulus and cognitive appraisal. Emotion is very important to entertainment application of virtual reality. Emotion model of 3D virtual characters is a challenging branch of Intelligent Virtual Environment (IVE). A believable 3D character should be provided with emotion and perception. In general, a virtual character is regarded as an autonomous agent with sense, perception, behavior and action. An emotion model of 3D virtual characters on the basis of psychology theory i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…For example, the intelligent AR tutor could be extended by integrating a virtual character into the tutoring environment. Research has shown that virtual characters can be beneficial in tutoring situations as they increase student motivation (Johnson et al 2000;Liu and Pan 2005;Gulz and Haake 2006). A 3D virtual character would allow the ITS to inhabit the world with the user, where it could give verbal instructions, make gestures and demonstrate installation procedures.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the intelligent AR tutor could be extended by integrating a virtual character into the tutoring environment. Research has shown that virtual characters can be beneficial in tutoring situations as they increase student motivation (Johnson et al 2000;Liu and Pan 2005;Gulz and Haake 2006). A 3D virtual character would allow the ITS to inhabit the world with the user, where it could give verbal instructions, make gestures and demonstrate installation procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Psychology and artificial intelligence are becoming new selling proposition of serious games [11]. It is realized that one of the technological innovations of next gen games would be modelling emotions [12]. However, only a few games have done this, e.g.…”
Section: Current Serious Games For Safety Educationmentioning
confidence: 99%
“…A normalized arousal valence score is computed through taking the mean rating divided by the standard deviation, (4) Afterward, for every quadrant in the normalized arousal valence space, the audio video stimuli that stimulus the happy and sad emotion is clearly determined and it lies at close quarters to the extreme corner of the quadrant. Figure 7 illustrates each audio video rating score with the selected emotion that is highlighted in blue for happy and brown for sad.…”
Section: Emotion Dimension Modelmentioning
confidence: 99%
“…[3] portray the used of emotion in interaction process, and revealed the latest techniques used to classify human emotions. [4] [5] [6] classified human emotion based on EEG signals along with arousal valence dimension model, they classified eight emotions toward with emotional model. [7] achieved the highest classification rate using emotion self-assessment classification technique, meanwhile, [8] and [9] have recognized and classified human emotion based on brain hemisphere activity variance, they determined a new approach for emotion classification based on brain hemisphere activity.…”
Section: Introductionmentioning
confidence: 99%